Sungai Larangan Sebagai Upaya Pelestarian Ikan Dan Lingkungan Berbasis Eduwisata Oleh KKN Tematik Universitas Mataram Di Desa Bilebante - Muhamad Haikhal; Nopia Lestari; Akhmad Saufi (Universitas Mataram, 2022)
Bilebante Village is one of the Green Tourism Villages located in Pringgarata Districs, Central Lombok Regency. Bilebante Village has various tourism potentials, one of which is the prohibition river. The prohibition river is a river area that has been mutually agreed upon as a place for conservation of fish and aquatic animals in the river area such as lizards, monitor lizards, snakes and so on as well as an educational-based tourist spot. Seeing this potential, the 2022 UNRAM Thematic KKN Students in Bilebante Village carried out a work program in building the prohibition river by making information boards containing awig-awig with the aim of being able to provide education regarding the importance of conservation fish and aquatic animals as well as those in the river area for visiting tourist to the prohibition river.